Staphylococcus aureus Isolates from Bovine Mastitis in Eight Countries: Genotypes, Detection of Genes Encoding Different Toxins and Other Virulence Genes - Monistero, Valentina (2018)
Staphylococcus aureus (S. aureus) is recognized worldwide as one of the major agent of dairy cow intra-mammary infections. This microorganism can express a wide spectrum of pathogenic factors used to attach, colonize, invade and infect the host. The present study considered 120 isolates from eight different countries that were investigated for 27 different virulence factors to increase the knowledge on the circulating genetic lineages among the cow population with mastitis. Among the virulence factors, fmtB, cna, clfA and leukotoxins genes were the most frequent. The sea and sei genes were present in seven out of eight countries; seh gene showed high frequency in South American countries while sel gene was harboured especially in Mediterranean countries. The etb, seb and see genes were not detected in any of the isolates, while only two isolates were MRSA confirming the low diffusion of methicillin resistance microorganism among bovine mastitis isolates. This work demonstrated the wide variety of S. aureus genotypes found in dairy cattle worldwide. This condition suggests that considering the region of interest might help to formulate strategies for reducing the infection spreading.